Hypothesizing Marine Provincialism on the Basis of Seaweed Distribution in Malaysia - J.L.S, Ooi; C.L, Wong; S.M, Phang (Malaysian Journal of Science, 2006)
Biogeographically, Malaysia is included in the Indo-West Pacific tropical marine region, which harbours the highest diversity of coral reefs, seagrasses and mangroves. We hypothesize that the Malaysian coastline may be divided into smaller spatial units in the order of provinces and districts in order to better understand the distribution patterns of marine biota. This paper will examine how the distribution pattern of seaweeds along the Malaysian coastline is clustered geographically at different taxonomic levels (family, genus, species). Data is sourced from field sampling (1984 - 2004) and published checklists. In this analysis, the Malaysian coastline is divided into five operational geographic units (OGU): (1) West Coast Peninsular Malaysia (2) East Coast Peninsular Malaysia (3) Sarawak (4) West Coast Sabah, and (4) East Coast Sabah. Sorensen's Similarity Index was calculated for each OGU. The results of this preliminary analysis show that (i) there was no distinction between any of the OGUs at the level of the family; (ii) at the genus level, there was a marked separation between the seaweed populace of Peninsular Malaysia and North Borneo; (iii) at the species level, all the OGUs are distinctly separated. The findings of this research tell us that in the case of seaweeds, provinces may best be reflected at the generic level, and districts at the species level.